3x+6(2)=x+11(4)

Simple and best practice solution for 3x+6(2)=x+11(4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6(2)=x+11(4) equation:


Simplifying
3x + 6(2) = x + 11(4)

Multiply 6 * 2
3x + 12 = x + 11(4)

Reorder the terms:
12 + 3x = x + 11(4)

Multiply 11 * 4
12 + 3x = x + 44

Reorder the terms:
12 + 3x = 44 + x

Solving
12 + 3x = 44 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
12 + 3x + -1x = 44 + x + -1x

Combine like terms: 3x + -1x = 2x
12 + 2x = 44 + x + -1x

Combine like terms: x + -1x = 0
12 + 2x = 44 + 0
12 + 2x = 44

Add '-12' to each side of the equation.
12 + -12 + 2x = 44 + -12

Combine like terms: 12 + -12 = 0
0 + 2x = 44 + -12
2x = 44 + -12

Combine like terms: 44 + -12 = 32
2x = 32

Divide each side by '2'.
x = 16

Simplifying
x = 16

See similar equations:

| 6x(2-3y)+7y=-21 | | 3ax-4x=0 | | 23=-3(5y+2) | | 66y/3-34y | | 8x^2-128x=0 | | 1+6y-15y= | | 1/3-K/8=7/24 | | -1(-1y+3)=1 | | -.4x^2+.2x=-2 | | 4x^2+10=-14x | | 2x^3/5=54 | | 3(x+4)+2x=2 | | 11-x=7+3x | | 5(0)-2=4-3(0)+2 | | 24=-3+6(v+7) | | 7(-3)+20=2(-3)+5 | | x^3=6x^2-36x-60 | | 7y^2-7=144 | | 9x^2-74x+16=0 | | -50-2x=-290 | | 6s+7-9s=31 | | X^2+5x+15x=0 | | t-1/3=1/4 | | -300m-4p=10p | | K^1/3/k^2/3k-1 | | 2f+8=3f-4 | | 3/1-√19 | | 2x=y/(y-1)-3 | | 2(3y-10)=4y+26 | | 23=2x+8+x | | (x-3)2+5x=(x+2)2-5 | | Q=5aP^2+9bP^3 |

Equations solver categories